2021
DOI: 10.20960/nh.03749
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional risk and clinical outcomes in critically ill adult patients with COVID-19

Abstract: Nutritional risk and clinical outcomes in critically ill adult patients with COVID-19Riesgo nutricional y resultados clínicos de pacientes adultos críticamente enfermos con

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
2
12
0
5
Order By: Relevance
“…Furthermore, mild malnutrition patients presented a significant hazard ratio with greater potential to discharge compared to malnourished patients. These results were similar to those evidenced by Martinuzzi et al ( 29 ) showing that longer hospital length of stay and longer ICU stay resulted from poor nutritional status as measured by subjective global assessment (SGA) and nutritional risk screening 2002 (NRS 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, mild malnutrition patients presented a significant hazard ratio with greater potential to discharge compared to malnourished patients. These results were similar to those evidenced by Martinuzzi et al ( 29 ) showing that longer hospital length of stay and longer ICU stay resulted from poor nutritional status as measured by subjective global assessment (SGA) and nutritional risk screening 2002 (NRS 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Li et al [29] showed that NUTRIC independently predicted the risk of hospital death (OR: 1.19, p=0.006) and the length of stay, but not considering obesity. Additionally, Martinuzzi et al [30] demonstrated that non-survivors had higher rates of comorbidities and higher nutritional score values (NRS, 2002) even when adjusted by obesity, as observed in our sample.…”
Section: Discussionsupporting
confidence: 80%
“…To minimise physical contact and the risk of nosocomial transmission, nutrition screening tools that do not require physical examination could be used to quantify malnutrition risk. Nutrition Risk Screening 2002 score ≥3 was associated with higher mortality risk in one prospective study (N=285) 7 but not in another retrospective study (N=286). 8 In the absence of a validated nutrition screening/ assessment tool that has good prognostic value and can be conducted without physical assessment, the utility of baseline nutrition screening/assessment can be questioned.…”
Section: Nutrition Assessmentmentioning
confidence: 80%